Evaluation of a CMOS Image Sensor and SRAM-Based FPGA for Space Applications - Hebrio, Ralph Ryan A. (2024)
The success of the first-generation Camera for Space Exploration (CASPEX) has been a vehicle in solidifying not only the use of Commercial Off The Shelf (COTS) components for space applications but also in extending the 3D Plus stacking technology and processes to the imaging domain. This, as well as the increasing importance of image sensors in space, became two of the main motivations for the development of its direct successor, the 12 Megapixel (MP) Space Camera Module. This study focuses on the evaluation of its most vulnerable components in the context of radiation which have been identified to be the CMOS Image Sensor and the SRAM-based FPGA.